PREVALENSI DAN HUBUNGAN SINDROM METABOLIK DENGAN PENYAKIT GINJAL KRONIK PADA POPULASI DESA LEGIAN, KUTA BALI - Ayu, Paramita; Kandarini, Yenny; Widiana, G Raka; Sudhana, W; Loekman, Jodhi S; Suwitra, K (journal of internal medicine, 2011)
Metabolic syndrome may relate to pathogenesis of chronic kidney disease (CKD). There is scarce data with regard to thatphenomenon in Indonesian general population. We conduct a study to determine the prevalence of metabolic syndrome and itsrelationship with CKD individuals in general population of Legian Village, Bali. An analytical cross sectional study was carriedout in the community of Legian Village, a tourist destination in Bali. Samples were selected through simple random sampling.Two hundred and eighty four samples (117 males and 107 females, aged 46.1 ± 10.02 years) were included. Prevalenceof hypertension, hypertrigliseridemia, hypoHDL-cholesterol, central obesity, impaired fasting glucose (IFG), obese and CKDwas 14.1%, 38.4%, 25%, 18%, 11.6%, 51.8% and 11.6% respectively. Using bivariate analysis, there were strong and significantrelationship between hypertension (OR 2.6, 95%CI 1.12 to 6.19, p = 0.02) and IFG (OR 5.21; 95%CI 2.23 to 12.13, p = 0.00) withCKD. Using multivariate logistic regression entering those components of metabolic syndrome into the model, it was consistentlyfound that hypertension and DM is the associated factors for CKD in the population. There was increasing odds of CKD about1,0-fold every augment of metabolic syndrome components (OR 1.098; 95%CI 0.83 to 1.44). As our conclusion, hypertensionand IFG are associated factor for CKD in general population. Multiple components increased risk factor for CKD.